2007
DOI: 10.1038/sj.emboj.7601495
|View full text |Cite
|
Sign up to set email alerts
|

aPKC-mediated phosphorylation regulates asymmetric membrane localization of the cell fate determinant Numb

Abstract: In Drosophila, the partition defective (Par) complex containing Par3, Par6 and atypical protein kinase C (aPKC) directs the polarized distribution and unequal segregation of the cell fate determinant Numb during asymmetric cell divisions. Unequal segregation of mammalian Numb has also been observed, but the factors involved are unknown. Here, we identify in vivo phosphorylation sites of mammalian Numb and show that both mammalian and Drosophila Numb interact with, and are substrates for aPKC in vitro. A form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
240
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(259 citation statements)
references
References 47 publications
17
240
1
1
Order By: Relevance
“…Numb is a negative regulator of Notch signaling [47] and regulates Notch endocytosis [48]. Numb has recently been shown to be phosphorylated by aPKCs [49], which prompted us to test whether the effect of PKCζ on Notch was influenced by Numb. Overexpression of Numb reduced Notch activity (Supplementary information, Figure S2), in keeping with previous reports [48].…”
Section: Apkcζ Increases Production Of Nicd Enhances Notch Signalingmentioning
confidence: 99%
“…Numb is a negative regulator of Notch signaling [47] and regulates Notch endocytosis [48]. Numb has recently been shown to be phosphorylated by aPKCs [49], which prompted us to test whether the effect of PKCζ on Notch was influenced by Numb. Overexpression of Numb reduced Notch activity (Supplementary information, Figure S2), in keeping with previous reports [48].…”
Section: Apkcζ Increases Production Of Nicd Enhances Notch Signalingmentioning
confidence: 99%
“…Miranda associates with the cortex via its cortical localization domain, but once this domain is phosphorylated by aPKC it is released into the cytoplasm leading to their mutually exclusive localization. Cortical association of the protein Numb is also modulated by aPKC phosphorylation, both in Drosophila and polarized mammalian cells (9), suggesting that coupling of aPKC-mediated phosphorylation to cortical displacement may be a general mechanism for Parmediated polarity.…”
mentioning
confidence: 99%
“…Through mechanisms that are still being elucidated, the Par complex becomes polarized to one cortical domain and keeps other, cell type-specific factors, localized to an opposite cortical domain (10 -12). The activity of aPKC is a key output of the Par complex because the association of substrates with the cortex can be modulated by phosphorylation (7)(8)(9). For example, in Drosophila neuroblasts the protein Miranda localizes to a cortical domain opposite the Par complex, and its polarization requires aPKC activity (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the 24 January issue of The EMBO Journal, Jane McGlade and colleagues reported that Numb is a substrate for aPKC, and that this phosphorylation is necessary to maintain its asymmetric localization in both mammalian epithelial cells and mitotic Drosophila SOP cells (Smith et al, 2007).…”
mentioning
confidence: 99%